WinCE-based embedded system for control of an industrial screw machine - Moreira, António H. J. (2009)
Nowadays, industrial systems frequently require the control of some industrial process and monitoring of relevant data about the process, using a friendly visual environment. Normally, is used a PLC (Programmable Logical Controller) to control the process and assure that the timing requirements (deadlines) are satisfied and a PC to monitor the data. However, the implementation of such solution presents the following drawbacks to the system programmer: (1) he or she needs to know the communication protocol between the two platforms - PLC and the PC; (2) he or she needs to learn two different programming languages - the low level PLC language and a high level PC language. On the other hand, in some cases, the reserved space to control the systems is reduced, making the implementation of such solution very hard. This paper presents an approach based on an embedded PC with real-time processing capability and data monitoring facility. The proposed system runs the Windows CE operating system and allows all software development in C/C++, using the Microsoft Visual Studio environment. The system was tested on an industrial screw machine for PCBs.